The U.S. Shale Boom and the Middle East - Makdessy, Rachel (2021)
For decades, the United States’ interests in the Middle East have been highly influenced by America’s need to secure the free flow of oil from the Persian Gulf region. Yet, while reliance on Middle East oil has restricted U.S foreign policy options towards the region, the surge in domestic shale oil and gas since late 2008 has brought unequivocal advantages for American statecraft. As U.S petroleum imports from the Middle East began to drop and shale oil found new grounds on global energy markets, the Obama administration came upon a significant political toolkit. The 2015 nuclear agreement with Iran has been termed President Obama’s ‘legacy’ in the Middle East. It has also brought to light the role of U.S shale oil in supporting American diplomacy and sanctioning endeavors against the Iranian regime. This thesis tackles this particular case as it showcases how capitalizing on this shale boom has provided President Obama with foreign policy options that were not attainable to his predecessor George W. Bush. The analysis offered complements theoretical paradigms in International Relations with empirical evidence on the role of energy politics. The thesis hence reveals how shale oil served as a geopolitical force supporting American actions against Iran as an oil-rich nation and a U.S adversary in the Middle East.